2020
DOI: 10.1097/htr.0000000000000521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preexisting and Co-Occurring Comorbid Conditions on Recovery in the 5 Years After Rehabilitation for Traumatic Brain Injury

Abstract: Objective: To determine the relationship between comorbid health conditions and the trajectory of functional recovery 5 years following traumatic brain injury (TBI) rehabilitation. Setting: Two acute rehabilitation facilities. Participants: A total of 407 patients with primary diagnosis of TBI. Design: Prospective, observational. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Estimates suggest that up to 25 percent of individuals who deployed in support of the wars in Iraq and Afghanistan likely have had a TBI (Lindquist, Love, and Elbogen, 2017). Although not all military-related TBIs are recorded, the U.S. Department of Defense (DoD) reports that more than 444,300 service members experienced a TBI between 2000 and 2021 (Corrigan et al, 2020;Military Health System, undated-a;Military Health System, undated-b;Traumatic Brain Injury Center of Excellence, 2021). Although some veterans with TBI recover completely, many have ongoing challenges related to their TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates suggest that up to 25 percent of individuals who deployed in support of the wars in Iraq and Afghanistan likely have had a TBI (Lindquist, Love, and Elbogen, 2017). Although not all military-related TBIs are recorded, the U.S. Department of Defense (DoD) reports that more than 444,300 service members experienced a TBI between 2000 and 2021 (Corrigan et al, 2020;Military Health System, undated-a;Military Health System, undated-b;Traumatic Brain Injury Center of Excellence, 2021). Although some veterans with TBI recover completely, many have ongoing challenges related to their TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive and specialized rehabilitation is considered beneficial after brain injury. 20 , 21 , 22 However, age, 23 , 24 , 25 functional status, 23 , 24 , 26 comorbidity burden, 27 , 28 and injury severity 29 have the potential to affect patients’ rehabilitation outcomes. Older adults with TBI in IRF differ from their younger counterparts in several of these areas, specifically, they are more likely to have mild brain injuries, 30 multiple chronic conditions, 31 and may have pre-injury declines in health that contributed to sustaining a TBI.…”
mentioning
confidence: 99%
“…1,2 A large civilian literature has demonstrated that the cumulative burden of health comorbidities after TBI is associated with increased functional decline, rehospitalization, and mortality. [1][2][3] Studies of long-term health outcomes after TBI in military veterans are inconclusive. Some studies report poorer overall health among veterans, [4][5][6][7] particularly those who experienced combat, [8][9][10] while others suggest that veterans have comparable or better health at the time of retirement 7,[11][12][13] and a lower risk of mortality 13 than nonveterans.…”
mentioning
confidence: 99%
“…PERSONS WITH TRAUMATIC BRAIN INJURY (TBI) are at an increased risk for poor long-term health outcomes, including comorbid health conditions and multimorbidity 1,2. A large civilian literature has demonstrated that the cumulative burden of health comorbidities after TBI is associated with increased functional decline, rehospitalization, and mortality 1–3. Studies of long-term health outcomes after TBI in military veterans are inconclusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation